Quantification of the variability between tacaco progenies (Sechium tacaco) - Monge Pérez, José Eladio (2018)
The variation in the morphological characteristics of fruits from two tacaco [Sechium tacaco (Pittier) C. Jeffrey] progenies was measured with referent to fruits of the original plant. The study was developed in Costa Rica. Ten quantitative variables were evaluated. There were statistically significant differences between fruits of the original plant and those of at least one of its two progenies for the following fruit variables: weight, length, width, number of incomplete longitudinal sutures, number of spines, length/width ratio, and width/thickness ratio. Conversely, there were no significant differences for fruit thickness, number of complete longitudinal fruit sutures, and fruit length/thickness ratio. This investigation provides the first known report in the literature regarding morphological variability in fruits of progenies of tacaco. These results yield evidence of the gene flowmagnitude in this species.